Organochlorine compound residues in muscle and liver tissues of Atlantic bluefin tuna (Thunnus thynnus L., 1758) - (:unkn) unknown (My University, 2008)
The aim of this study is to investigate organochlorine compound (OC) residues in muscle and liver tissues of Atlantic bluefin tuna (Thunnus thynnus L., 1758). The OC residues were analysed in fish liver and muscle tissues by GC-ECD and confirmed by GC-MS. OC residue levels were compared to reported values from similar studies conducted in the other Mediterranean countries. The OC levels in the tissues of Atlantic bluefin tuna were lower than the level limited by Turkish Food Codes. The analysed OC residues were found in all samples at mean concentrations under the permissible limits proposed by FAO/WHO. As a result, there was no serious hazard in the samples in terms of the OC residues analysed from the Gulf of Antalya, the Mediterranean Sea, Turkey.
Keywords: Ecotoxicology; Marine pollution; Mediterranean sea; Organochlorine